Gestão de projetos especiais em uma universidade comunitária (PUC-SP): análise de uma situação concreta - Veiga, Windsor Espenser (2009)
The research examines Special Projects at university and aspects of its management. The concept of Special Projects is developed during this study. It addresses what are these projects and their management, limits and possibilities, and also, aspects of monitoring and evaluation of financial and human resources applied. Projects for various purposes are present in the most varied social and corporative entities, and are being increasingly found in universities, which are appropriate and effective spaces of learning processes in several fields of knowledge. It is observed that the scenario of demands of the globalized world is increasingly complex, and one possibility is the opening of universities for Special Projects to understand and meet these needs through partnerships signed by agreements or contracts. To achieve the proposed objectives, it was adopted as methodology the documental and bibliographical search, approaching the qualitative research, becoming an exploratory study. The research finds the routing and management procedures of Special Projects in the Pontifícia Universidade Católica de São Paulo, community university, using aspects of the PEC Programa de Educação Contínua Continuing Education Program, and observes if there was academic improvement among those involved, checking the flow of procedures and aiming the academic and administrative performance. To support it, were studied works and concepts of administrators, managers and educators who contributed to the development of scientific education and to the management of projects, there was also the contribution of people interviewed, professionals from the university searched. Subsequently, the factors were described, aggregators or not, to the limits and possibilities related to the management of Special Projects in a community university, the academic, administrative and financial contributions, the eyes of some units and departments involved, and the possibility of the Special Projects to become a source of additional resources, institutional interaction, social purpose, training and qualification in service and of institutional projection